2018
DOI: 10.2478/folmed-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Can Wearable Devices Accurately Measure Heart Rate Variability? A Systematic Review

Abstract: Wearable devices may provide a promising alternative solution for measuring RV. However, more robust studies in non-stationary conditions are needed using appropriate methodology in terms of number of subjects involved, acquisition and analysis techniques implied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
181
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(188 citation statements)
references
References 44 publications
4
181
0
3
Order By: Relevance
“…Currently, novel ECG monitoring technologies are being developed in the hopes of providing more convenient long‐term heart rate monitoring. Studies have found that wearable devices may provide a promising solution for heart rate monitoring; however, more robust studies in nonstationary conditions are required . Wearable ECG devices that have been developed include sensor sites on the chest, ear, hand, wrist, torso, leg, or thigh .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, novel ECG monitoring technologies are being developed in the hopes of providing more convenient long‐term heart rate monitoring. Studies have found that wearable devices may provide a promising solution for heart rate monitoring; however, more robust studies in nonstationary conditions are required . Wearable ECG devices that have been developed include sensor sites on the chest, ear, hand, wrist, torso, leg, or thigh .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that wearable devices may provide a promising solution for heart rate monitoring; however, more robust studies in nonstationary conditions are required . Wearable ECG devices that have been developed include sensor sites on the chest, ear, hand, wrist, torso, leg, or thigh . In addition, ECG monitoring devices involving fewer leads have also been developed to allow easier and more cost‐effective ways to conduct short repeated assessments.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, technology exists for measuring heart rate in the form of optical photoplethysmogram (PPG). However, this technology cannot accurately detect heart rhythm [8]. Some emerging devices are providing ECG based functionality; however, these devices rely on the user touching the device on their wrist with their other hand in order to establish a bipolar lead.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there have been reports that the PPG sensor, used to measure HR and HRV in wearable devices is susceptible to motion noise (Baek & Shin, ). As motion increases, correlations decrease due to motion artifacts (Georgiou et al, ). This is an important issue that developers of wearable devices need to address, since the purpose of these devices are to be worn while a person goes about their daily life, which involves a multitude of movements.…”
Section: Discussionmentioning
confidence: 99%